2014 IEEE International Electric Vehicle Conference (IEVC) 2014
DOI: 10.1109/ievc.2014.7056145
|View full text |Cite
|
Sign up to set email alerts
|

Fully electric city buses - The viable option

Abstract: Key challenges in traffic systems are carbon footprint of the vehicles, local emissions, noise and congestion. Fully electric city buses offer a solution to these challenges in public inner city transport. At the same time, electric buses open up for a lower total cost of ownership (TCO) provided that the vehicle, charging infrastructure and new operating concepts are designed and considered together. This is based on the fact that high utilisation rates of the expensive battery systems can be reached in comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 2 publications
0
27
0
1
Order By: Relevance
“…The residual indicates that there were some factors left unconsidered. Pihlatie et al [1] noted that 6% and 12% of the BEB consumption is caused by aerodynamic drag and the use of mechanical brakes, respectively. In our previous study, we found that up to 18% of the ECR variation of BEBs is caused by rolling resistance variation and 13% by payload variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The residual indicates that there were some factors left unconsidered. Pihlatie et al [1] noted that 6% and 12% of the BEB consumption is caused by aerodynamic drag and the use of mechanical brakes, respectively. In our previous study, we found that up to 18% of the ECR variation of BEBs is caused by rolling resistance variation and 13% by payload variation.…”
Section: Discussionmentioning
confidence: 99%
“…Battery electric buses (BEBs) have recently emerged as an environmentally friendly, yet expensive alternative for diesel buses [1]. In addition to the high initial investment, the life cycle costs (LCC) depend on the selected charging strategy (e.g., overnight vs. opportunity charging) and the selected battery capacity that is defined by the charging strategy [2].…”
Section: Introductionmentioning
confidence: 99%
“…The calculated TCO of the diesel bus is 1.44 €/km, including environmental costs 0.05 €/km. It should be noted that in some studies, in which the comparison of the buses is performed [11], labour costs, insurance costs and vehicle tax are not included in the TCO calculation, whereas in this study all costs related to owning, operation and maintenance of the bus are considered in the TCO. For the diesel bus, investment costs form 28% of total TCO.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, plug-in and battery-swapping e-buses are more suitable for suburban routes [30]. In summary, to neutralize the environmental impact of public transportation, replacing a conventional bus system with an e-bus transportation system would minimize the required number of ebuses and charging stations and the level of battery capacity, thereby streamlining the use of e-buses and decreasing the overall cost of the replacement [28,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 97%